2006
DOI: 10.1001/archinte.166.13.1396
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function and Heart Failure Risk in Older Black and White Individuals

Abstract: The association of kidney dysfunction with heart failure appears stronger in blacks than for whites, particularly when cystatin C is used to measure kidney function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 36 publications
(38 reference statements)
4
34
0
4
Order By: Relevance
“…This association was independent of obesity, baseline glucose, eGFR (or serum creatinine), ACR, and other explanatory variables. These results extend previous observations for CVD (17,18,20,32,33) to include the early diabetic stage.…”
Section: Results -supporting
confidence: 90%
See 1 more Smart Citation
“…This association was independent of obesity, baseline glucose, eGFR (or serum creatinine), ACR, and other explanatory variables. These results extend previous observations for CVD (17,18,20,32,33) to include the early diabetic stage.…”
Section: Results -supporting
confidence: 90%
“…Currently used estimating equations are poor at identifying early renal impairment and better indexes are of great interest (15,16). Recently, several studies have suggested that cystatin C levels may be a more sensitive marker of early renal impairment than either albuminuria or serum creatinine concentration (17)(18)(19)(20). Cystatin C is a novel measure of kidney function that seems to overcome the limitations of serum creatinine concentration.…”
mentioning
confidence: 99%
“…Consistent with these findings, CKD has been reported to result in a significantly greater increase in risk for coronary artery disease mortality or incident congestive heart failure among blacks than white individuals. 18,19 In our study, death was the only outcome measure studied, and we were unable to demonstrate any interaction between race and CKD.…”
Section: Discussionmentioning
confidence: 57%
“…2,18,19 Thus, efforts to increase detection and recognition of decreased GFR have been the focus of national and international campaigns. In these analyses, we found that the presence of eGFR Ͻ60 ml/ min per 1.73 m 2 was only associated with elevated risk of death, cardiovascular events, and heart failure if it was confirmed by cystatin C. Persons with decreased GFR by creatinine alone had equivalent risks to persons without decreased GFR.…”
Section: Discussionmentioning
confidence: 99%